Capture the growth kinetics of CVD growth of two-dimensional MoS2 - Zhu, Dancheng; Shu, Haibo; Jiang, Feng; Lv, Danhui; Asokan, Vijayshankar; Omar, Omar; Yuan, Jun; Zhang, Ze; Jin, Chuanhong (NPJ 2D materials and applications, 2017)
Understanding the microscopic mechanism is fundamental for function-oriented controlled chemical vapor deposition growth of two-dimensional (2D) materials. In this work, we reveal the growth kinetics of 2D MoS 2 by capturing the nucleation seeds, evolving morphology, edge structure, and edge terminations at the atomic scale during chemical vapor deposition growth using the transmission electron microscopy and scanning transmission electron microscopy. The direct growth of few-layer and mono-layer MoS 2 onto graphene-based transmission electron microscopy grids helped us to perform the subsequent transmission electron microscopy characterization without any solution-based transfer. Two seeding centers are observed: (i) Mo-oxysulfide (MoO x S 2− y ) nanoparticles either in multi-shelled fullerene-like structures or as compact nanocrystals for the growth of fewer-layer MoS 2 ; (ii) Mo-S atomic clusters. In the early stage growth, irregular polygons with two primary edge terminations, S-Mo Klein edges and Mo zigzag edges, appear approximately in equal numbers. The morphology evolves into a near-triangle shape in which Mo zigzag edges predominate. Results from density-functional theory calculations are consistent with the inferred growth kinetics, and thus support the growth mechanism we proposed. In general, the growth mechanisms found here should also be applicable in other 2D materials, such as MoSe 2 , WS 2 and WSe 2 . 2D molybdenum disulfide under the microscope The growth kinetics of two-dimensional (2D) molybdenum disulfide (MoS 2 ) atomic layers has been captured using atomic-resolution transmission electron microscopy (TEM). In a regular process, 2D growth is usually performed on a silicon dioxide substrate. This makes studying the atomic-scale structures difficult because small layers can be damaged while transfering onto TEM grids. A team led by Chuanhong Jin at Zhejiang University, China, grew atomic layers of MoS 2 directly on graphene-layer-based TEM grids in a regular chemical vapor deposition system. With this method intermediate and few-nanometer scale layers have been successfully monitored. These results are important for understanding the growth mechanism of MoS 2 and other relevant 2D materials.